DIVERSITY OF FISH AT SEAGRASS ECOSYSTEM IN BINTAN ISLAND WATERS AND SORROUNDING AREA - Aditya Hikmat Nugraha; Sari Wahyuni; Fadhliyah Idris; Ahmad Zahid (Politeknik Kelautan dan Perikanan Dumai, 2023)
Seagrass ecosystems are components of coastal ecosystems that play roles in life, such as habitat, spawning ground, and feeding ground for the marine organism, including fishes. The purpose of this study was to describe the composition of fishes associated with seagrass ecosystems in the waters of Bintan Island and its surroundings. A total of four observation stations, namely Setumu Coast, Dinsos Coast, Bantu Empang Coast, and Malang Rapat Coast. Fish sample were collected in each station using gill nets 100 m in length and mesh size of 1.5 inches. The collected fish sample were identified and counted for relative abundance. Based on this research, the fish species collected in this research comprised 26 species. The highest abundance of fish was found in the Batu Empang coast station in Pengudang Village. Pengudang Village has a very high percentage of seagrass cover. The individual highest abundance is Siganus canaliculatus, commonly found in Malang Rapat coast. This species has depend on the seagrass ecosystems highly.